Efficacy and safety of a parylene-coated occluder for atrial septal defect: a prospective, multi-center, randomized controlled clinical trial. Issue 22 (20th November 2021) - Yang, Kai; Lyu, Jian-Hua; Hu, Hai-Bo; Wu, Wen-Hui; Zhang, Ge-Jun; Jin, Jing-Lin; Liu, Yu-Hao; Feng, Yuan; Wang, Li-Ming; Zhao, Shi-Hua; Jiang, Shi-Liang; Li, Wei; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Nitinol-containing devices are widely used in clinical practice. However, there are concerns about nickel release after nitinol-containing device implantation. This study aimed to compare the efficacy and safety of a parylene-coated occluder vs . a traditional nitinol-containing device for atrial septal defect (ASD). Methods: One-hundred-and-eight patients with ASD were prospectively enrolled and randomly assigned to either the trial group to receive a parylene-coated occluder ( n  = 54) or the control group to receive a traditional occluder ( n  = 54). The plugging success rate at 6 months after device implantation and the pre- and post-implantation serum nickel levels were compared between the two groups. A non-inferiority design was used to prove that the therapeutic effect of the parylene-coated device was non-inferior to that of the traditional device. The Cochran–Mantel–Haenszel chi-squared test with adjustment for central effects was used for the comparison between groups. Results: At 6 months after implantation, successful ASD closure was achieved in 52 of 53 patients (98.11%) in both the trial and control groups (95% confidence interval (CI): [−4.90, 5.16]) based on per-protocol set analysis. The absolute value of the lower limit of the 95% CI was 4.90%, which was less than the specified non-inferiority margin of 8%. No deaths or severe complications occurred during 6 months of follow-up. The serum nickel levels were significantly increased at 2 weeks and reached the maximum value at 1 month after implantation in the control group ( P  < 0.05 vs . baseline). In the trial group, there was no significant difference in the serum nickel level before vs . after device implantation ( P  > 0.05). Conclusions: The efficacy of a parylene-coated ASD occluder is non-inferior to that of a traditional uncoated ASD occluder. The parylene-coated occluder prevents nickel release after device implantation and may be an alternative for ASD, especially in patients with a nickel allergy.